2009
DOI: 10.1055/s-0029-1214610
|View full text |Cite
|
Sign up to set email alerts
|

Do endoscopy capsules interfere with implantable cardioverter-defibrillators?

Abstract: The clinical use of the three tested capsule devices is safe in patients with ICDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 9 publications
1
19
0
Order By: Relevance
“…A capsule endoscope such as the PillCam and EndoCapsule employs radiofrequencies of 434 MHz pulsed with 2 or 4 Hz as their transmission method [19], which is equivalent to a heart rate of 120 or 420 beats/min that represents slow ventricular tachycardia to ventricular fibrillation. Therefore, cardiac devices may recognize non-existent heart signals from the capsule endoscope and inhibit ventricular pacing, which may cause bradycardia and symptomatic dizziness or syncope.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A capsule endoscope such as the PillCam and EndoCapsule employs radiofrequencies of 434 MHz pulsed with 2 or 4 Hz as their transmission method [19], which is equivalent to a heart rate of 120 or 420 beats/min that represents slow ventricular tachycardia to ventricular fibrillation. Therefore, cardiac devices may recognize non-existent heart signals from the capsule endoscope and inhibit ventricular pacing, which may cause bradycardia and symptomatic dizziness or syncope.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies demonstrated that CE does not significantly interfere with cardiac devices [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Consecutively, in 9 of 20 patients (45%) the question of the study, in how far SBCE would influence pacemakers, could not be answered, as the pacemakers cannot be influenced at all. Considering to our study [2] without evidence of interference between CE and implantable cardioverter defibrillators (ICDs) it remains unclear, why the sensing function of the ICDs was turned off.…”
Section: To the Editormentioning
confidence: 90%
“…Oversensing may be developed by the radio frequencies of 434 MHz pulsed with 2 or 4 Hz used in capsule endoscopy as a transmission method, because the frequency is equivalent to a heart rate of 120 or 420 beats/min that represents slow ventricular tachycardia to ventricular fibrillation [69]. Therefore, cardiac devices may recognize it as nonexisting heart signals and inhibit ventricular pacing, which may cause bradycardia and symptomatic dizziness or syncope.…”
Section: Clinical Studies Of Mirocammentioning
confidence: 99%
“…If cardiac device cannot recognize the actual heart signal, it fails to deliver an appropriate therapy with potential induction of asynchronous ventricular or noisemode function and tachyarrhythmia will continue. However, these effects have not been observed to this time in vitro or clinical studies of conventional capsule endoscope [69][70][71][72][73][74][75][76]. Because, the vector of RF transmission with capsule endoscope is mostly within the abdomen, where is far from the location of the cardiac devices [71].…”
Section: Clinical Studies Of Mirocammentioning
confidence: 99%